Palladium(II)-Catalyzed Sequential C−Cl Bond Formation: A Novel and Efficient Method for Direct α,α-Dichlorination of β-Dicarbonyl Compounds - Liu, Weibing; Tan, Liquan; Zhou, Peng; Chen, Cui; Zhang, Qing (Synthesis, 2013)
A simple and concise procedure for the synthesis of 2,2-dichloro-3-oxo-N-phenylbutanamides, via palladium-catalyzed C(sp3)–H dichlorination of 3-oxo-N-phenylbutanamides, is described. The protocol provides a direct route to α,α-dichlorinated products starting from β-dicarbonyl compounds. A plausible mechanism for this transformation involving two consecutive chlorination steps is described.
Keywords: 2,2-dichloro-3-oxo-N-phenylbutanamides; β-dicarbonyl compounds; dichlorination; carbon–chlorine bond